ITRAQ-Based Proteomic Analysis of Visual Cycle-Associated Proteins in RPE of rd12 Mice before and after RPE65 Gene Delivery. (1st June 2015) - Zheng, Qinxiang; Ren, Yueping; Tzekov, Radouil; Hua, Shanshan; Li, Minghan; Pang, Jijing; Qu, Jia; Li, Wensheng
Abstract : Purpose. To investigate the iTRAQ-based proteomic changes of visual cycle-associated proteins in RPE of rd12 mice before and after RPE65 gene delivery. Mehtods . The right eyes of rd12 mice underwent RPE65 gene delivery by subretinal injection at P14, leaving the left eyes as control. C57BL/6J mice were served as a wide-type control group. ERGs were recorded at P42, and RPE-choroid-sclera complex was collected to evaluate the proteomic changes in visual cycle-associated proteins by iTRAQ-based analysis. Western blot was used to confirm the changes in the differentially expressed proteins of interest. Results . ERG parameters improved dramatically at P42 after RPE65 delivery. The proteomics analysis identified a total 536 proteins with a global false discovery rate of 0.21%, out of which 7 were visual cycle-associated proteins. RALBP-1, RBP-1, and IRBP were reduced in the untreated rd12 eyes and the former two were improved after gene therapy, confirmed by Western blot analysis. Conclusions . RPE65 gene delivery restored retinal function at P42 and modified the expression of other functional proteins implicated in the visual cycle. The level of RALBP-1 was still below the normal level after gene therapy in rd12 mice, which may explain the delayed dark adaption in LCA patients undergoing similar therapy.